Pengembangan Komponen Instrumen Terpadu (KIT) Praktikum Pada Materi Larutan Penyangga - Filandari, Mia; Wiwit, Wiwit; Rohiat, Salastri; Krisandini, Triana (FKIP University of Mataram, 2025)
This research is developing an integrated instrument component (KIT) practicum on buffer solution material. The study aimed to determine the feasibility level of the KIT developed and the students' response to the KIT. The development model is carried out by using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The research was conducted in May 2022 at SMA Negeri 5 Kota Mukomuko. The trial class selection was conducted through purposive sampling of all XI MIPA classes, with 12 students from the XI MIPA 2 class participating in small-scale trials and 30 students from the XI MIPA 1 class in large-scale trials. Data collection methods were carried out using written tests and student response questionnaires. The data obtained were analyzed using validation tests, response questionnaire analysis, and an examination of student learning outcomes. The results obtained (1) KIT practicum is very feasible to be used as a practicum media by students based on the results of validation tests on media and material aspects, (2) The response of students to the trial of the KIT practicum of buffer solution is included in the very interesting category shown in the acquisition of an average value of 86.6%.